Multigroup analysis using SmartPLS: step-by-step guidelines for business research - Cheah, Jun Hwa; Thurasamy, Ramayah; Memon, Mumtaz Ali; Chuah, Francis; Ting, Hiram (MAG Scholar, 2020)
Multigroup Analysis (MGA) using partial least squares path modelling (PLSPM) is an efficient approach to evaluate moderation across multiple relationships in a research model. This editorial explains the importance and the usage of MGA, especially when a study intends to understand heterogeneity effects (i.e., cross-cultural or gender differences) in a business research. We provide step-by-step guidelines to perform MGA using SmartPLS 3.3.2, including the assessment of measurement invariance using the measurement invariance of composite models (MICOM) procedure. We believe that this editorial will enable researchers and postgraduate students to conduct MGA with confidence to draw meaningful insights from the data and examine the differences across the groups under investigation.